GlnR-Mediated Regulation of Short-Chain Fatty Acid Assimilation in Mycobacterium smegmatis - Liu, Xin-Xin; Shen, Meng-Jia; Liu, Wei-Bing; Ye, Bang-Ce (Frontiers in Microbiology, 2018)
Assimilation of short-chain fatty acids (SCFAs) plays an important role in the survival and lipid biosynthesis of Mycobacteria. However, regulation of this process has not been thoroughly described. In the present work, we demonstrate that GlnR as a well-known nitrogen-sensing regulator transcriptionally modulates the AMP-forming propionyl-CoA synthetase (MsPrpE), and acetyl-CoA synthetases (MsAcs) is associated with SCFAs assimilation in Mycobacterium smegmatis, a model Mycobacterium. GlnR can directly activate the expression of MsprpE and Msacs by binding to their promoter regions based upon sensed nitrogen starvation in the host. Moreover, GlnR can activate the expression of lysine acetyltransferase encoding Mspat, which significantly decreases the activity of MsPrpE and MsAcs through increased acylation. Next, growth curves and resazurin assay show that GlnR can further regulate the growth of M. smegmatis on different SCFAs to control the viability. These results demonstrate that GlnR-mediated regulation of SCFA assimilation in response to the change of nitrogen signal serves to control the survival of M. smegmatis. These findings provide insights into the survival and nutrient utilization mechanisms of Mycobacteria in their host, which may enable new strategies in drug discovery for the control of tuberculosis.